2018
DOI: 10.1155/2018/6020197
|View full text |Cite
|
Sign up to set email alerts
|

A Network Pharmacology‐Based Approach to Investigate the Novel TCM Formula against Huntington’s Disease and Validated by Support Vector Machine Model

Abstract: Several pathways are crucial in Huntington's disease (HD). Based on the concept of multitargets, network pharmacology-based analysis was employed to find out related proteins in disease network. The network target method aims to find out related mechanism of efficacy substances in rational design way. Traditional Chinese medicine prescriptions would be used for research and development against HD. Virtual screening was performed to obtain drug molecules with high binding capacity from traditional Chinese medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The pharmacodynamic mechanisms of TCM against liver fibrosis have multiple levels and multiple targets and pay attention to the characteristics of overall regulation [10]. A new approach that analyzes TCM with network pharmacology may be a reliable way to overcome disease [49]. Cumulating data have shown that network pharmacology can reveal the interactions between multiple targets of compounds present in Chinese herbal medicines [50].…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacodynamic mechanisms of TCM against liver fibrosis have multiple levels and multiple targets and pay attention to the characteristics of overall regulation [10]. A new approach that analyzes TCM with network pharmacology may be a reliable way to overcome disease [49]. Cumulating data have shown that network pharmacology can reveal the interactions between multiple targets of compounds present in Chinese herbal medicines [50].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are no treatments that can slow or stop the progression of the disease. Dai et al [ 233 ] also employed the same network pharmacology-based methodology to explore a novel herbal formula against Huntington’s disease, which was then further validated by a support vector machine model. The authors demonstrated that Brucea javanica , Dichroa febrifuga , E. micranthum Harms , Erythrophleum guineense , Holarrhena antidysenterica , and Japanese Ardisia Herb contained active compounds that might be a novel medicine formula for Huntington’s disease.…”
Section: Application Of Network Pharmacology: From Understanding Of C...mentioning
confidence: 99%
“…Each created data set may indicate the quantitative variation of between 5,000 and 10,000 experimental indices (transcripts, proteins, or metabolites), with perhaps 100s-1000s of these being statistically significant. In this context the ability of an individual scientist to appreciate the connectivity between these factors, which likely represents the true biomedical and pharmacological meaning of the data, is profoundly limited without the assistance of machine-based clustering and annotation (Chen et al, 2018;Dai et al, 2018;Lee et al, 2018;Lin et al, 2018;Lim and Xie, 2019). While the intrinsic depth of such data streams is a tremendous analytical advance for the study of complex drug activities, a major hurdle for the clinical translation of such data are the pace of advanced data management and investigational platform development.…”
Section: Management Of High-dimensionality Experimental Datamentioning
confidence: 99%
“…In addition to the application of data deconvolution to identify key factors within complex networks, graphbased pipelines have been used to define drug-signaling pathway association analytics. For example, Dai et al (2018) defined a computational process, integrative graph regularized matrix factorization, to enhance the drug-induced signaling cascade classification and prioritization. Integrative graph regularized matrix factorization employs graph regularization to encode data geometrical information and prevent possible overfitting in the prediction of the association of specific therapeutic agents with the strongest associated signaling paradigm.…”
Section: Graph Theory Implementation For Signaling Network Decomentioning
confidence: 99%